Effect of the Digital Education Package (DEP) on prevention of anxiety in hospitalized children: a quasi-experimental study - Masoumeh Zamani; Abdolhosein Emami Sigaroudi; Moluk Pouralizadeh; Ehsan Kazemnejad-Leili (BMC, 2022)
Abstract Background Hospitalization of children is a stressful event. However, the child's education at the time of hospital admission can be effective for the prevention of their anxiety via the use of more attractive methods. The study's aim was to assess the effectiveness of the education using a digital education package on the level of anxiety of hospitalized children. Methods This is a quasi-experimental study with the randomized block method. The sample size was calculated based on Shahrabadi et al.'s study and sixty eligible hospitalized children were allocated to the two study groups from June 2019 to December 2020, in Hefdah-e-Sahrivar hospital which is the central pediatric hospital in Rasht city. The intervention was education using a digital package that was done 15 min after the hospitalization of the children. Pediatrics' Spielberger's anxiety Inventory was used for measuring the participants' anxiety before and after the intervention. We used Chi square test, Fisher exact test and paired t-test to analyze data. A p-value < 0.05 was considered statistically significant. Results In the post-intervention phase, total mean scores of anxiety were significantly lower in the experimental group (60.17 ± 6.46) rather than in the control group (72.6 ± 8.83) (P < 0.001). The mean anxiety scores before and after the intervention were 87.43 ± 11 vs. 60.17 ± 6.46 in the intervention group and 81.5 ± 11 vs. 72.6 ± 8.83 in the control group, respectively. There were significant differences in intergroup anxiety scores between the two study groups (P < 0.001). Conclusions The current study showed that the Digital Education Package (DEP) is an effective method for reducing children's anxiety during hospitalization. Therefore, we recommended it as a preferred and simple method rather than routine education for pediatric nurses.